Intra-abdominal hypertension in horses - Canola, P. A. [UNESP]; Johnson, P. J. (Wiley, 2013)
Intra-abdominal hypertension (IAH) may lead to a multiple organ dysfunction syndrome associated with significant dysfunction of the cardiovascular, respiratory, renal, gastrointestinal and central nervous systems of human patients. A recent prospective multicentre epidemiological investigation in man concluded that IAH was associated with an increased risk of mortality in critically ill patients. In this review, we present current information pertaining to the potential clinical importance of IAH in the context of equine clinical practice. In conclusion, consideration of intra-abdominal pressure should be a part of the clinical assessment of patient well-being in critically ill equine patients. © 2011 EVJ Ltd.
Keywords: Abdominal compartment syndrome; Horse; Indirect measurement; Intra-abdominal hypertension; Intra-abdominal pressure; Equidae